Importancia de las prácticas pre profesionales para los estudiantes de educación superior en la Universidad de Guayaquil - Guarnizo Crespo, Steve Freddy (2018)
This document seeks to determine the importance of pre-professional practices in higher education students at the University of Guayaquil, related to their preparation for employment, focusing on different positions, conceptualizations, opinions, criteria, in what concerns This activity complements the academic training of university students, as well as seeks to analyze the interaction of the actors involved in this process of student education. The scope of this research encompasses the main actors of this academic process, which involve the regulations imposed by the state towards highereducation institutions, and all the actors of the university, such as administrative staff, teachers and students. Interactive way they develop the practical formation that the student makes in his academic trajectory. The purpose of this document is to propose the awareness of the actors involved in this process of pre-professional practices, so as to understand the benefit of a good execution of the development of the practice for the benefit of the student to face the different expectations that are offer in the labor market